Optimization of RI-MP2 Auxiliary Basis Functions for 6-31G and 6-311G Basis Sets for First-, Second-, and Third-Row Elements - Tanaka, Masato; Katouda, Michio; Nagase, Shigeru (Journal of computational chemistry, 2013)
Auxiliary basis functions for second‐order Møller–Plesset perturbation theory with resolution‐of‐identity approximation (RI‐MP2) are developed for first‐, second‐, and third‐row elements, which are suitable for Pople‐type 6‐31G** and 6‐311G** basis sets. Atomic‐centered Gaussian functions up to the g‐type function are used for auxiliary basis functions to obtain higher accuracy for molecules with the accurate description of bonding properties. The performance of the developed auxiliary basis functions were tested and evaluated for 114 small and 23 large molecules. The developed auxiliary basis functions show much smaller energy differences between MP2 and RI‐MP2 than other auxiliary basis functions used for 6‐31G** and 6‐311G** basis sets with similar computational costs. © 2013 Wiley Periodicals, Inc. The RI‐MP2 auxiliary basis functions suitable for 6‐31G** and 6‐311G** basis sets are developed. Performance of the auxiliary basis functions is assessed for 114 small and 23 large molecules such as valinomycin (168 atoms). The largest resolution‐of‐identity (RI) errors (E(2)RI‐MP2 −E(2)MP2) for 6‐31G** and 6‐311G** basis sets are only 0.809 and 1.895 mHartree, respectively. The developed auxiliary basis functions are applicable to the second‐order Møller–Plesset perturbation theory with RI (RI‐MP2) calculations of very large molecules with high accuracy.